Not so "smart"? An Australian experiment in smart specialisation. (18th August 2021) - Weller, Sally; Rainnie, Alistair
Abstract: This article explores the utility of applying the European policy of smart specialisation to tackle spatial divergence in the Australian context. Using a geographical political economy approach and considering a growing literature on innovation in peripheral places, the work explores how smart specialisation is applied in Victoria's Latrobe Valley, a coal‐dependent non‐metropolitan industrial enclave in the Gippsland region. Analysis of the case suggests that market‐based growth processes envisaged by the architects of innovation‐based regional policies such as smart specialisation have been unable to spur development in Australia's disadvantaged non‐metropolitan regions. On the contrary, without more careful appreciation of local contexts, such policies will lead to further spatial divergence and exacerbate divisions between urban and regional communities. Abstract : This article explores the application of smart specialisation in Victoria's Latrobe Valley. It suggests that smart specialisation's focus on market‐based endogenous growth processes is ill‐equipped to spur development in Australia's disadvantaged non‐metropolitan regions. On the contrary, without more careful appreciation of local contexts, such policies will lead to further spatial divergence and exacerbate divisions between urban and regional communities.